Colonoscopic full-thickness resection using an over-the-scope device: a prospective multicentre study in various indications. Issue 7 (10th August 2017) - Schmidt, Arthur; Beyna, Torsten; Schumacher, Brigitte; Meining, Alexander; Richter-Schrag, Hans-Juergen; Messmann, Helmut; Neuhaus, Horst; Albers, David; Birk, Michael; Thimme, Robert; Probst, Andreas; Faehndrich, Martin; et al.
Abstract : Objective: Endoscopic full-thickness resection (EFTR) is a novel treatment of colorectal lesions not amenable to conventional endoscopic resection. The aim of this prospective multicentre study was to assess the efficacy and safety of the full-thickness resection device. Design: 181 patients were recruited in 9 centres with the indication of difficult adenomas (non-lifting and/or at difficult locations), early cancers and subepithelial tumours (SET). Primary endpoint was complete en bloc and R0 resection. Results: EFTR was technically successful in 89.5%, R0 resection rate was 76.9%. In 127 patients with difficult adenomas and benign histology, R0 resection rate was 77.7%. In 14 cases, lesions harboured unsuspected cancer, another 15 lesions were primarily known as cancers. Of these 29 cases, R0 resection was achieved in 72.4%; 8 further cases had deep submucosal infiltration >1000 µm. Therefore, curative resection could only be achieved in 13/29 (44.8%). In the subgroup with SET (n=23), R0 resection rate was 87.0%. In general, R0 resection rate was higher with lesions ≤2 cm vs >2 cm (81.2% vs 58.1%, p=0.0038). Adverse event rate was 9.9% with a 2.2% rate of emergency surgery. Three-month follow-up was available from 154 cases and recurrent/residual tumour was evident in 15.3%. Conclusion: EFTR has a reasonable technical efficacy especially in lesions ≤2 cm with acceptable complication rates. Curative resection rate for early cancers was too low to recommend its primary use in this indication. Further comparative studies have to show the clinical value and long-term outcome of EFTR in benign colorectal lesions. Trial registration number: NCT02362126; Results.